Jane Austen and the Enlightenment - Knox-Shaw, Peter, 1944- (Cambridge University Press, 2004)
In this first ever study of Jane Austen and the Enlightenment, Peter Knox-Shaw draws out the Enlightenment principles and ideas which lie behind much of Austen's writing. His study offers a startling new perspective on Austen, and is essential reading for all those interested in Austen and her writing.